Collaboration Between Fintech and Regional Government In The Village MSME Incubation Program To Increase Their Competitiveness - Sumardi, Sumardi; Mambu, Joupy G.Z.; Sari, Vina Budiarti Mustika; Zuhri, Saifuddin; Susilawati, Susilawati (Journal Of Human And Education (JAHE), 2024)
Abstrak Artikel ini bertujuan untuk mengetahui kolaborasi fintech dan pemerintah daerah dalam program inkubasi UMKM desa untuk meningkatkan daya saingnya. Kegiatan pengabdian kepada masyarakat melalui program inkubasi umkm Desa Balingasal Kecamatan Padureso Kabupaten Kebumen Jawa Tengah bertujuan untuk mengedukasi masyarakat khususnya UMKM tentang penggunaan fintech yang belum secara maksimal digunakan dalam hal peningkatan daya saing UMKM di desa. Implementasi program Inkubasi UMKM Desa Balingasal Kecamatan Padureso Kabupaten Kebumen Jawa Tengah menggunakan metode pelatihan dan pembekalan pada Jumat, 23 Februari 2024. Hasil kegiatan ini menunjukkan bahwa peserta kegiatan UMKM memiliki pengetahuan baru atau teredukasi tentang perkembangan dan keberadaan fintech, jenis-jenis fintech, manfaat dari penggunaan fintech serta apa saja keunggulan dari fintech. Peserta juga dibekali pelatihan tentang penggunaan fintech untuk meningkatkan daya saing UMKM dengan memanfaatkan jasa keuangan online. Program fintech pemerintah Kabupaten Kebumen berbentuk Kredit Usaha Rakyat (KUR) yang dapat diakses secara online oleh masyarakat melalui laman tpakd.kebumenkab.go.id. Kata Kunci: Inkubasi UMKM, fintech, pemerintah daerah Abstract This article aims to determine the collaboration between fintech and local government in the village MSME incubation program to increase their competitiveness. Community Service Activities (PKM) through the MSME incubation program in Balingasal Village, Padureso District, Kebumen Regency, Central Java, aims to educate the community, especially MSMEs, about the use of fintech which has not yet been used optimally in terms of increasing the competitiveness of MSMEs in the village. Implementation of the MSME Incubation program in Balingasal Village, Padureso District, Kebumen Regency, Central Java using training and provision methods on Friday, February 23 2024. The results of this activity show that MSME activity participants have new knowledge or are educated about the development and existence of fintech, types of fintech, the benefits of the use of fintech and what are the advantages of fintech. Participants are also provided with training on the use of fintech to increase the competitiveness of MSMEs by utilizing online financial services. The Kebumen Regency government's fintech program is in the form of People's Business Credit (KUR) which can be accessed online by the public via the tpakd.kebumenkab.go.id page. Keywords: Incubation of MSMEs, fintech, local government